Evaluation of survival across several treatment lines in metastatic colorectal cancer: Analysis of the FIRE-3 trial (AIO KRK0306). (October 2017) - Modest, D.P.; Ricard, I.; Stintzing, S.; Fischer von Weikersthal, L.; Decker, T.; Kiani, A.; Vehling-Kaiser, U.; Al-Batran, S.-E.; Heintges, T.; Kahl, C.; Seipelt, G.; Kullmann, F.; et al.
Abstract: Background: We explored the impacts of sequential application of various treatment lines on survival kinetics. Therefore, differences in overall survival (OS) observed in FIRE-3 were investigated in the context of time and exposure to applied treatment. Patients and methods: OS analyses (stratified by treatment with FOLFIRI plus either cetuximab or bevacizumab) were performed according to time intervals as well as using a Cox model to define changes of hazard ratio (HR) over time. Results: The fraction of patients with systemic treatment and time on treatment markedly decreases over treatment lines and time. OS evaluation by a Cox model indicated a trend towards a non-proportional hazard between treatment arms (P = 0.12/P = 0.09 for KRAS –intention-to-treat (ITT)/all- RAS wild-type populations, respectively). To improve the fit of the model, a change-point (point of curve separation) was estimated at 22.6 months (day 687) after randomisation. The HR between the two arms before 22.6 months was not significantly different from one. However, markedly different survival kinetics in favour of the cetuximab arm were apparent after the change-point ( KRAS -ITT: P = 0.0018; HR, 0.60 [95% confidence interval [CI], 0.44–0.83] and RAS : P = 0.0006; HR, 0.51 [95% CI, 0.35–0.75]). Conclusion: The differences in OS favouring the cetuximab arm become apparent about 22.6 months after randomisation, indicating that only those patients who survive 22.6 months after randomisation benefit from the superiority of the cetuximab arm. When OS curves separate, only few patients receive active systemic treatment in short courses, suggesting that earlier treatment effects are responsible for later kinetics of survival curves. Highlights: There is a trend for a non-proportional hazard in survival of FIRE-3. A change-point of the curves is at 22.6 months after randomisation. Only few patients receive active therapy at this point. Early treatments cause long-term effects in metastatic colorectal cancer.